The Renewal of the Kibbutz : From Reform to Transformation - Russell, Raymond (Book collections on Project MUSE., 2013)
This book explores the waves of kibbutzim reforms since 1990. Looking through the lens of organizational theories that predict how open or closed a group will be to change, the authors find that the less successful kibbutzim were the most receptive to reform, and reforms then spread through imitation from the economically weaker kibbutzim to the strong. Survey data is used to understand which reforms were the most common and which were most successful.